Funktionsweise und Replikationstil europäischer Exchange Traded Funds auf Aktienindices - Thomas Heidorn; Michael Winker; Christian Löw (Frankfurt School of Finance & Management, 2010)
Exchange Traded Funds (ETF) were established in Europe in 2000 and have grown to a size of over 200 bn US. Some issuers use a full replication strategy while others prefer a swap based approach. The ETF are dealt parallelly in the primary and in the secondary market, as new ETFs can be created at any time. Therefore, the market is very liquid with small ask bid spreads. The fees are considerably lower compared to active managed fonds. For liquid share indices both strategies can replicate the index convincingly. In the EUROSTOXX the ETF can outperform the Index due to dividend and tax optimization. This was not possible for the Dax. For illiquid large indices (MSCI Emerging Markets), there was a considerable difference between the monthly returns of the index compared to the ETFs. Both strategies have counterparty risk. The full replication uses security lending to enhance the performance. The synthetic strategy can have losses up to 10% if the swap partner defaults.
Keywords: 330; ETF; Exchange Traded Funds; Full Replication; Swap Replication; ETF Performance; ETF Risk